Metode Pemulusan Eksponensial Tripel Tipe Brown pada Peramalan Jumlah Produksi Kelapa Sawit Kabupaten Agam - Fatma Yulia Sari; Nonong Amalita; Helma Helma (UNIVERSITAS NEGERI PADANG, 2018)
Abstract –This research discusses the forecasting of the amount of palm oil production in Agam Regency by using Brown's exponential smoothing method. The problem that occurs is the amount of palm oil production in the future is not fixed (constant) or uncertain every year. Therefore, forecasting method can be the right solution in estimating the amount of palm oil production in the future. The purpose of this research is to estimate the amount of oil palm production of Agam Regency for the next five years. The method used to forecast the amount of Agam palm oil production is the Brown's exponential smoothing method. In this method, forecasting is done to predict the amount of oil palm production whether it has increased or decreased.